Comparison of maize seeders concerning the acquisition price and operational efficiency - Rocha, Francisco Eduardo de Castro; Mantovani, Evandro Chartuni; Bertaux, Serge; Garcia, J. C. (Pesquisa Agropecuaria Brasileira, 1992)
Eight maize seeders were evaluated concerning their prices, efficiency of their seed and fertilizer distribution mechanisms and planting depth control system. Regardless of the operation speed, the efficiency of these systems did not present so many variation among them. However, their acquisition price were very different, specifically, from dipping plate type seeders to pneumatic and finger pickup type seeders. The prices were taken for the same size seeders and the evaluated efficiencies did not justify the so big price difference among them.
Keywords: Zea mays; mechanization; mechanized seeding; economical aspects